Genotype analysis of hepatitis B virus in the Turkish population using restriction fragment length polymorphism patterns - (:unkn) unknown (My University, 2001)
Objective: Six different HBV genotypes have been defined comparing the complete HBV genome. The distribution of genotypes among infected populations varies geographically. A relationship between HBV genotypes and the development of chronic liver disease has been proposed. Therefore, this study was designed to classify HBV genotypes in the Turkish population using restriction fragment length polymorphism (RFLP) analysis of the S gene region. Methods: The HBV DNA extracted from forty-eight serum samples were subjected to polymerase chain reaction (PCR) using primers from the S region of HBV genome. Restriction enzymes, Hph I (Genotype F), Nci I (Genotype E), Alw I (Genotype C), Ear I (Genotype B), and Nla IV (Genotype A and D), were used for RFLP analysis of amplified product of HBV DNA. Results: In the 48 serum samples investigated, 3 different genotypes were detected. These were as follows; Genotype D: 41 (85.41%), Genotype A: 5(10.41%), and Genotype F: 2 (4.16%). Conclusion: This study shows a molecular heterogeneity of HBV in the Turkish population with at least 3 different genotypes observed in the 48 samples studied. The genotype D was by far the most common genotype in the Turkish population as is the case in all other Mediterranean countries.
Keywords: Genotypes; Hepatitis B virus; Restriction fragment length polymorphism; S gene